The mediation of gay men's lives: A review on gay dating app studies. Issue 2 (15th January 2018) - Wu, Shangwei; Ward, Janelle
Abstract: A growing body of literature focuses on gay men's use of mobile dating applications or "dating apps." Running on smartphones and working with GPS, dating apps connect users to others in close geographic proximity and often in real time. These apps allow users to create profiles to present themselves and interact with each other to reach multiple goals, such as casual sex, dating, or networking. Attending to the dynamics between communication technologies and society, this article reviews gay dating app studies that highlight the communicative practices and social relations mediated by dating apps. Using the mediation framework as a starting point, we examine major themes in these studies, including gay men's online self‐presentation and interactions, gay community in the digital era, and gay men's interpersonal relationships. We suggest that future research should pay more attention to the technical development of dating devices and the transformation of gay men's social relations.